Bacterial nanocellulose as novel additive in low-lipid low-sodium meat sausages. Effect on quality and stability. (October 2017) - Marchetti, Lucas; Muzzio, Bianca; Cerrutti, Patricia; Andrés, Silvina C.; Califano, Alicia N.
Graphical abstract: Highlights: Bacterial nanocellulose (BNC) a novel biopolymer has great potential in meat industry. A more solid-like matrix was developed when BNC was added to meat emulsions. BNC increased water-binding properties, hardness, cohesiveness, and chewiness. Good stability of the products with BNC during 45-days of storage was achieved. BNC addition resulted into a suitable fat mimetic in low-fat emulsified meat systems. Abstract: Replacing animal fat with different oils has been proposed to improve fatty acid profile of meat emulsions. In this work a novel application of bacterial nanocellulose (BNC, 0–0.534 g of dry BNC/100 g batter) to low-lipid low-sodium meat emulsions formulated with pre-emulsified high-oleic sunflower oil is discussed. Process yield, water content, water activity, water holding capacity, color, texture, rheological characteristics, microstructure, and shelf-life were analyzed. Thermo-rheological curves showed a typical meat system gelation behavior where BNC addition produced a more solid-like three-dimensional network. Environmental Scanning Electron Micrographs of the systems revealed microstructure modifications in accordance with these results. Water-binding properties, hardness, cohesiveness, and chewiness increased when up to 0.267 g of dry BNC/100 g batter was added, while further additions had a negative impact on these attributes. Thus using oil pre-emulsified with BNC as fat mimetic had no negative effect on the quality properties of low-fat low-sodium meat sausages. A 45-days shelf-life under vacuum refrigerated storage was assured for this product.